Invert biopanning: A novel method for efficient and rapid isolation of scFvs by phage display technology. Issue 6 (November 2016) - Rahbarnia, Leila; Farajnia, Safar; Babaei, Hossein; Majidi, Jafar; Veisi, Kamal; Tanomand, Asghar; Akbari, Bahman
Abstract: Phage display is a prominent screening technique for development of novel high affinity antibodies against almost any antigen. However, removing false positive clones in screening process remains a challenge. The aim of this study was to develop an efficient and rapid method for isolation of high affinity scFvs by removing NSBs without losing rare specific clones. Therefore, a novel two rounds strategy called invert biopanning was developed for isolating high affinity scFvs against EGFRvIII antigen from human scFv library. The efficiency of invert biopanning method (procedure III) was analyzed by comparing with results of conventional biopanning methods (procedures I and II). According to the results of polyclonal ELISA, the second round of procedure III displayed highest binding affinity against EGFRvIII peptide accompanied by lowest NSB comparing to other two procedures. Several positive clones were identified among output phages of procedure III by monoclonal phage ELISA which displayed high affinity to EGFRvIII antigen. In conclusion, results of our study indicate that invert biopanning is an efficient method for avoiding NSBs and conservation of rare specific clones during screening of a scFv phage library. Novel anti EGFRvIII scFv isolated could be a promising candidate for potential use in treatment of EGFRvIII expressing cancers.